2012
DOI: 10.1111/j.1467-8268.2012.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Remittances' Influence on Housing Construction Demand in Sub‐Saharan Africa: The Case of Kenya

Abstract: Although it is well documented that immigrants maintain economic and social ties with their communities of origin through remittances, the role of remittances in asset acquisition for most African countries is yet to be documented. This study provides empirical estimates for the impact of remittances from abroad on housing construction demand in Kenya using time series data for the period 1970-2008. An autoregressive distributed lag (ARDL) modelling process is employed to capture the effect of remittances and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
2
12
1
Order By: Relevance
“…Also in SSA, saving and investment respond significantly to remittance flows (Baldé, ) and remittances have poverty‐reducing effect in Africa (Anyanwu and Erhijakpor, ). Remittances increase the demand for housing in Kenya (Kagochi and Kiambigi, ). Other evidence presented by Salisu () suggests that remittances encourage capital outflows in Africa.…”
Section: Related Literaturementioning
confidence: 99%
“…Also in SSA, saving and investment respond significantly to remittance flows (Baldé, ) and remittances have poverty‐reducing effect in Africa (Anyanwu and Erhijakpor, ). Remittances increase the demand for housing in Kenya (Kagochi and Kiambigi, ). Other evidence presented by Salisu () suggests that remittances encourage capital outflows in Africa.…”
Section: Related Literaturementioning
confidence: 99%
“…We use housing quality as our measure of welfare as there is strong body of evidence that suggests that remittances are often invested in the improvement of housing (e.g. Kagochi and Kiambigi 2012, Osili 2004, Durand et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…According to Adams and Cuecuecha (), households receiving remittances spend more at the margin on investment goods because they treat their remittance earnings as transitory (rather than permanent) income, and the marginal propensity to invest out of transitory income is higher than that for other sources of income. For instance, Kagochi and Kiambigi () found that remittances are one of the important drivers of construction demand in Kenya.…”
Section: Review Of the Literaturementioning
confidence: 99%